On the determination of the real exchange rate in free markets: Do consumer risk-pooling and uncovered interest parity differ and fit? - Patrick Minford; Zhirong Ou; Zheyi Zhu (Cardiff University, Cardiff Business School, 2023)
We revisit the "puzzle" in open economy studies that evidence of international risk-sharing is hardly seen despite the completeness of the financial market. We reassess both risk-pooling via state-contingent bonds, and uncovered interest parity - both were believed to be different, and spuriously rejected, in previous work - in the context of a full DSGE model. We prove that the two models are identical, both analytically and numerically. When tested as part of the full DSGE model by indirect inference which circumvents the bias of single-equation tests, we find strong and wide evidence of international risk-sharing.
Keywords: C12; E12; F41; 330; consumer risk-pooling; UIP; two-country DSGE model; indirect inference test